Current Status of Nutrition Training in Graduate Medical Education From a Survey of Residency Program Directors: A Formal Nutrition Education Course Is Necessary. (11th February 2015) - Daley, Brian J.; Cherry‐Bukowiec, Jill; Van Way, Charles W.; Collier, Bryan; Gramlich, Leah; McMahon, M. Molly; McClave, Stephen A.; ,
Abstract : Introduction: Nutrition leaders surmised graduate medical nutrition education was not well addressed because most medical and surgical specialties have insufficient resources to teach current nutrition practice. A needs assessment survey was constructed to determine resources and commitment for nutrition education from U.S. graduate medical educators to address this problem. Methods: An online survey of 36 questions was sent to 495 Accreditation Council for Graduate Medical Education (ACGME) Program Directors in anesthesia, family medicine, internal medicine, pediatrics, obstetrics/gynecology, and general surgery. Demographics, resources, and open‐ended questions were included. There was a 14% response rate (72 programs), consistent with similar studies on the topic. Results: Most (80%) of the program directors responding were from primary care programs, the rest surgical (17%) or anesthesia (3%). Program directors themselves lacked knowledge of nutrition. While some form of nutrition education was provided at 78% of programs, only 26% had a formal curriculum and physicians served as faculty at only 53%. Sixteen programs had no identifiable expert in nutrition and 10 programs stated that no nutrition training was provided. Training was variable, ranging from an hour of lecture to a month‐long rotation. Seventy‐seven percent of program directors stated that the required educational goals in nutrition were not met. The majority felt an advanced course in clinical nutrition should be required of residents now or in the future. Conclusions: Nutrition education in current graduate medical education is poor. Most programs lack the expertise or time commitment to teach a formal course but recognize the need to meet educational requirements. A broad‐based, diverse universal program is needed for training in nutrition during residency.